Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Please explain me the idea of differentiating differential forms (tensors). Example: compute d(xdy + ydx) The answer is known, we should have 0. What's the rule?

share|improve this question
1  
Hint: a differential form is a bit like a product. How do you differentiate a product? –  Asal Beag Dubh Mar 18 '13 at 18:02
add comment

3 Answers

up vote 4 down vote accepted

There is a formula of computing exterior derivative of any differential form (which is assumed to be smooth). In your case, if $\sigma$ is a 1-form, and $$ \sigma = \sum_{j=1}^n f_j \mathrm{d}x^j. $$ Then the exterior derivative of $\omega$ is: $$ \mathrm{d}{\sigma} =\sum_{j=1}^n \sum_{i=1}^n \frac{\partial f_j}{\partial x^i} \mathrm{d}x^i \wedge \mathrm{d}x^j . $$

Following this formula the exterior derivative of the 1-form you gave is: $$ \begin{aligned} \mathrm{d}(x\mathrm{d}y + y\mathrm{d}x)&= \mathrm{d}(x\mathrm{d}y) + \mathrm{d}(y\mathrm{d}x) \\ &= \left(\frac{\partial x}{\partial x}\mathrm{d}x\wedge\mathrm{d}y + \frac{\partial x}{\partial y}\mathrm{d}y\wedge\mathrm{d}y\right) + \left(\frac{\partial y}{\partial x}\mathrm{d}x\wedge\mathrm{d}x + \frac{\partial y}{\partial y}\mathrm{d}y\wedge\mathrm{d}x\right) \\ &= (\mathrm{d}x\wedge\mathrm{d}y+0) + (0+ \mathrm{d}y\wedge\mathrm{d}x)=0. \end{aligned}$$ Notice we used $\mathrm{d}x^i\wedge\mathrm{d}x^i = 0$ and $\mathrm{d}x^i\wedge\mathrm{d}x^j= -\mathrm{d}x^j\wedge\mathrm{d}x^i$.

share|improve this answer
    
at the second addend of first bracket should be dy^dy if I understood you in a right way –  maggot092 Mar 18 '13 at 18:21
    
@maggot092 Yes, thanks for correcting the typo. –  Shuhao Cao Mar 18 '13 at 19:31
add comment

Visually, the differential of a differential form

$$ \color{red}{f} \, \color{blue}{\text{d}x} $$

is determined by taking the differential the function part $f$ (in red) in place:

$$ \text{d}(\color{red}{f} \, \color{blue}{\text{d}x}) = \color{red}{\text{d}f} \, \color{blue}{\text{d}x} $$

if you write wedge products out expictly, you need to insert a wedge:

$$ \text{d}(\color{red}{f} \, \color{blue}{\text{d}x}) = \color{red}{\text{d}f} \wedge \color{blue}{\text{d}x} $$

The same is true with higher forms:

$$ \text{d}(\color{red}{f} \, \color{blue}{\text{d}x\,\text{d}y}) = \color{red}{\text{d}f} \, \color{blue}{\text{d}x \, \text{d}y} $$

And, of course, the differential distributes across sums as usual.

Because the double differential $\text{d}(\text{d}f) = 0$ for all functions $f$ (and $\text{d}(\text{d}\omega)$ is also true for all differential forms $\omega$), $\text{d}f$ behaves very much like a constant; e.g. it factors out of the derivative. The only trick is that it's not commutative, so you have to make sure it factors out on the correct side: to the right, not to the left.

This all can be viewed as a special case of the product rule

$$ \text{d}(\omega \theta) = (\text{d} \omega)\, \theta + (-1)^{\deg \omega} \omega \, (\text{d}\theta) $$

where $\deg \omega$ is the 'degree' of the form $\omega$: it is $n$ if $\omega$ is an $n$-form (and so $0$ if $\omega$ is a scalar).

Alternatively, written with wedge products:

$$ \text{d}(\omega \wedge \theta) = (\text{d} \omega) \wedge \theta + (-1)^{\deg \omega} \omega \wedge (\text{d}\theta) $$

share|improve this answer
add comment

You have:

$d(xdy + ydx)=dx\wedge dy+ x\wedge d^2 y+ dy\wedge dx+y\wedge d^2 x=dx\wedge dy +dy\wedge dx=0$.

For the general formula see (for example): Calculus on manifolds (Spivak)

http://books.google.fr/books?id=POIJJJcCyUkC&printsec=frontcover&source=gbs_atb#v=onepage&q&f=false

Manuel.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.